DEVELOPING WEBQUEST FOR TEACHING WRITING RECOUNT TEXT FOR THE 10TH GRADERS IN MA BILINGUAL BATU - As Syifa (Language-Edu, 2021)
The aim of this study is to developing a WebQuest for teaching writing recount text to the tenth graders. This product using Research and Development (R&D) adapted from Hyland (2013) which consist of need an analysis, product development, expert validation, first revision, product tryout, second revision and final product. This product was validating by a lecture of English Department in Brawijaya University and an English teacher of MA Bilingual Batu. The WebQuest was create by using google site and divided into seven sections such as introduction task, process, evaluation, conclusion, resources, and teacher page. The result showed that this product of WebQuest was suitable for teaching writing recount text.